2019
DOI: 10.3390/jcm8060766
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biofeedback Usefulness in Masticatory Muscle Activity Management—A Systematic Review

Abstract: Temporomandibular disorders (TMD) have multifactorial and complex etiology. Regardless of their etiology, all those conditions may result in centrally mediated chronic muscle pain, myalgia, myofascial pain, myofibrotic contracture, myosistis, myospasm, headache and a variety of neck, shoulder, upper back and lower back pain. Biofeedback (BF) is one of methods that has been used for more than 50 years in rehabilitation to facilitate normal movement patterns after injuries. Some studies suggest that biofeedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…This phenomenon appears to be analogous to deprogramming and creating new muscle engrams [ 33 , 34 ]. T-scan III might prove useful in clinical procedures as an occlusal biofeedback [ 35 , 36 ]. This may be of great importance in the case of people who, due to occlusal reasons, have consciously changed their chewing pattern (one-sided chewing, bypassing selected anatomical units in the chewing cycle) and, consequently, overload the structures of the masticatory system.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon appears to be analogous to deprogramming and creating new muscle engrams [ 33 , 34 ]. T-scan III might prove useful in clinical procedures as an occlusal biofeedback [ 35 , 36 ]. This may be of great importance in the case of people who, due to occlusal reasons, have consciously changed their chewing pattern (one-sided chewing, bypassing selected anatomical units in the chewing cycle) and, consequently, overload the structures of the masticatory system.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of patients with TMD suffer from clinical conditions such as disc displacement, arthralgia, osteoarthrosis, and osteoarthritis (Warren and Fried, 2001;Wadhwa and Kapila, 2008). TMDs have a complex and multifactorial etiology (Florjanski et al, 2019). Mechanical loading has been shown to contribute to their onset and progression (Holyoak et al, 2019), and metabolismrelated dysbiosis and the accumulation of inflammatory cytokines might also be involved in disease pathogenesis (Wadhwa and Kapila, 2008;Park and Chung, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the literature concludes that biofeedback can be useful in helping to manage masticatory muscle activity. Most of the studies showed a significant correlation between the use of biofeedback and the reduction of masticatory muscle activity (18).…”
Section: Discussionmentioning
confidence: 99%